Economic management mechanism of agricultural enterprise: theoretical and methodological aspect - Семенова, А. Ю. (Scientific Progress & Innovations, 2012)
The essence and the structure of the economic management mechanism of agricultural enterprise is considered. The conclusion has been made on the basis of generalizing different approaches concerning term «economic mechanism» and its specifics – economic methods of management which function basing on giving and refusing material (financial) reward. At the same time they leave freedom of making choice of behavior variants for the management object and just create conditions stimulating to achieve the set goals. The necessity of creating economic management mechanism in competitive environment is stressed.